Konsep Hukum Islam Rohmatan Lil Alamin Sebagai Dasar Moderasi Beragama di Indonesia - Sapri Ali (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2023)
One of the biggest threats that can divide a nation is religious conflict, let alone using violent means. However, for everyone who is excessively fanatical about religion, it is understood as something holy, noble, sacred and sacred. Even if in reality Religion comes to earth and brings Benefit to humanity, but he will be able to show a different face when manifested with a fanatical mind and full of emotion. Instead of doing good, followers of religious fanatics can get caught up in bad attitudes offending the spirit of religion itself. To avoid this conflict, it is necessary to build religious tolerance in Indonesia, which is very important to do to prevent and reduce the phenomenon of intolerance that occurs. In building tolerance to overcome various conflicts that occur, religious moderation is something that must be done. Religious moderation means teaching religion not only to form pious individuals personally, but also to be able to make their religious understanding an instrument to respect people of other religions. Islam in seeing diversity is something that is necessary and a reality of human life. This article is a library research so that in its discussion it uses books, books, journals and articles related to the discussion of religious moderation. The procedure for collecting information is a search for documents from relevant up-to-date sources as well as a bibliography. Methods of analysis of information analysis activities in this model include: information reduction, information presentation, and drawing/validating conclusions. The information obtained is tested by analyzing the contents of the theme to produce appropriate answers (solutions). The concept of Islamic law "rahmatan lil alamin" is a very important and relevant concept in the context of religious moderation in Indonesia. The concepts offered by Islam are: Wasathiyah (taking the middle way), Tawazun (balanced), I'tidal (straight and firm), Musawah (equality), Syuro (deliberation), Ishlah (reform), Awlawiyah (prioritizing priority) , Tathawur Wa Ibtikar (dynamic and innovative), Tahadhdhur (Civilized). This concept encourages Indonesian people to respect and accept differences, as well as promote peace and tolerance among religious communities. In this case, the Indonesian government and people must continue to strengthen and apply this concept to ensure the realization of a just, peaceful and civilized society.